POSDEM: Un software para optimizar la selección y estimación en el diseño de encuestas por muestreo probabilístico. Ilustración con una encuesta sobre el profesorado - Sánchez-Crespo, Gonzalo; Lezcano Lastra, Alberto (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
POSDEM application has been designed to optimize the sampling selection. For several sampling methods, this software, allows to answer questions like: what selection procedure is it better for a specific population frame?; and the sampling size related with a significance level?; what is the mean square error?; what are the units that must be investigated? The help files could be used like a book of sampling techniques. An illustration with a student population has been prepared with the purpose to show the possibilities of this software.